A palaeopathological example of Legg-Calvé-Perthes disease from Argentina - Ponce, Paola (2014)
Legg-Calvé-Perthes (LCP) disease is a very uncommon condition that affects one in 10,000 paediatric patients. Examples described in the palaeopathological literature are scarce and for this reason the exceptional examples found in archaeological contexts are worthy of analysis, description and reporting. We record an archaeological example from Argentina, skeleton 12 Cápiz Alto (12 CA) that shows skeletal signs compatible with this condition.